PEMANFAATAN BUAH PISANG BATU SEBAGAI BAHAN BAKU PEMBUATAN BREM DI DESA PENARUKAN KECAMATAN KERAMBITAN KABUPATEN TABANAN - GUNAWAN, I WY. G; KARDA, I MD; SUYASA, I W. BUDIARSA (Buletin Udayana Mengabdi; Vol 5 No 1 (2006): Volume 5 No.1 – April 2006, 2012)
ABSTRACT One of the beverage types nowadays likely drunk by lots of Bali society is brem representing alcohol beverage to be made through ferment process. Process of brem fermentation basically is to change reduction sugar which is on stone banana become alcohol with catalyst by enzyme yielded by yeast. If it is evaluated from economic facet, the fact that stone banana represents standard material of good brem producer besides it is cheap and also easy to get and if processed become brem beverage will assign enough high nutrition value with alcohol rate 5 ? 10 %. Brem beverage alcohol rate is highly depended on some factors like amount of side-result, amount of sugar used by yeast, yeast amount and type having the character of fermentative, loss of alcohol because of evaporation, and existence of air resulting the happening of oxidation. Degradation of alcohol rate caused by the happening of continuation ferment, that is alcohol turned into acetate acid because happened reaction of estherification. Process of this estherification always happened so that making alcohol rate and organic acids go down To obtain brem beverage with well guaranteed quality, hence process of specially process ferment cover : fermentation, maturation and pasteurizes (aging) require obtaining furthermore observation and attention.